Pengaruh Penerapan Sistem Informasi Akuntansi dan Motivasi Kerja terhadap Kinerja Pegawai Unit Pelaksana Teknis Daerah Pusat Kesehatan Masyarakat Kabupaten Aceh Barat - Tinambunan, Rumena; Rahmadani, Ika; Rahmazaniati, Linda; Risnafitri, Hafidzhah; Mahdani, Rimal (Medan Resource Center, 2024)
This study investigates the effect of accounting information system implementation and work motivation on employee performance at the Unit Pelaksana Teknis Daerah Pusat Kesehatan Masyarakat of Aceh Barat Regency. The research is motivated by the need to improve employee performance in public health institutions amid increasing demands for accountability, efficiency, and service quality. Using a quantitative research design, this study involved 39 employees as the total population and research sample. Data were collected through structured questionnaires and analyzed using multiple linear regression techniques. Instrument validity was assessed using Pearson correlation, while reliability was examined through Cronbach’s alpha. Hypothesis testing was conducted using the coefficient of determination, t-tests, and F-tests. The findings reveal that both the accounting information system and work motivation have a significant effect on employee performance, either partially or simultaneously. These results indicate that effective utilization of accounting information systems, combined with strong employee motivation, contributes substantially to improving performance in public health service organizations. The study concludes that strengthening information systems and fostering work motivation are essential strategies for enhancing employee performance and organizational effectiveness in the public sector.